Sosialisasi Pelestarian Dan Pengelolaan Cagar Budaya di Kota Pematang Siantar - Hisarma Saragih (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
The Pematang Siantar city government has issued Regional Regulation number 1 of 2021 concerning the Preservation and Management of Cultural Conservation in the city of Pematang Siantar. Cultural heritage is a cultural heritage that is material in the form of Cultural Conservation Objects, Cultural Conservation Buildings, Cultural Conservation Structures, Cultural Conservation Sites, and Cultural Conservation Areas on land and or in water that need to be preserved because they have important values for history, science, education, religion, and or culture through the determination process. The purpose of this community service is to explain to participants, namely government employees in the sub-districts of Pematang Siantar city, which are eight sub-districts so that they can know and get provisions to carry out the preservation and management of cultural heritage or suspected cultural heritage in their respective regions.The method used is the lecture method, followed by a question and answer session between the lecturer and the participants. The lecture was conducted by displaying a slide that could show an image of a suspected cultural heritage at the Office of Education and Culture of Pematang Siantar City Jl. Merdeka, Pematang Siantar. The result achieved in this socialization is that participants consisting of government employees in the sub-district can recognize a number of objects that are suspected of being cultural heritage in their working areas. Sustainability of socialization means that sub-district employees are equipped with abilities, and are able to take action in the effort to preserve and manage cultural heritage, or those suspected of cultural heritage by the community to sub-district employees to be followed up. The mandate of the Pematang Siantar Mayor's Regional Regulation number 1 of 2021 can be applie